Assessing the influence of the dimensions of taqwa on affective commitment: the case of Tabung Haji in Malaysia - Sulaiman, Mohamed; Zainudin, Dolhadi; Shahuddin, Shaffina; Mohammed Kamil, Naail (Conference Master Resources, 2013)
The relationship between organizational commitment and other work-related attitudes has received enormous attention from studies in the West. There is dearth of research investigating the relationship between organizational commitment and other cross-cultural or religious perspectives, especially the Islamic perspective. The present research attempts to empirically study the relationship between the Affective component of the organizational commitment construct and Taqwa from the Islamic management perspectives. The data employed for this study was drawn from 230 Muslim employees of Lembaga Tabung Haji in Malaysia. Factor Analyses followed by Multiple Regression analyses were conducted to study the relationship between the dependent (Affective commitment) and the independent (Taqwa) variables. It was shown that Affective commitment has direct significant relationship with the Islamic Social Responsibility (ISR) dimension of Taqwa but not with the Islamic Spirituality (IS) dimension of Taqwa.